2016
DOI: 10.1016/j.carbon.2015.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Li and H dynamics in Li6C60 and Li6C60H

Abstract: We report the extensive investigation of Li and H dynamics in Li 6 C 60 and Li 6 C 60 H y , by combining 7 Li and 1 H solid state NMR measurements with DC/AC conductivity, in order to evaluate the potential application of these systems for energy-storage purposes. 7 Li NMR results show a local motion of Li ions above 200 K in both pristine and hydrogenated compounds, with activation energies of 90-150 meV and correlation times of about 30 ps. Evidences of Li interdiffusive dynamics are given by conductivity me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 29 publications
7
28
2
Order By: Relevance
“…The last step is the slowest because, when LiD reacts with the hydrofulleride (Li 6-α C 60 D 8+y-α ), the limiting process is the ionic diffusion of Li + in the deuterated phase which is reported to be slow. 14 In order to confirm this hypothesis we fit the time evolution of the integrated intensity of the Li 6 The temperature is shown on the right y-axes. 16 The fit is shown in Figure 6 and yields k = 8.4(6) % h -1 , t i = 8.28(1) h, and n = 0.537 (3).…”
Section: Discussionmentioning
confidence: 93%
“…The last step is the slowest because, when LiD reacts with the hydrofulleride (Li 6-α C 60 D 8+y-α ), the limiting process is the ionic diffusion of Li + in the deuterated phase which is reported to be slow. 14 In order to confirm this hypothesis we fit the time evolution of the integrated intensity of the Li 6 The temperature is shown on the right y-axes. 16 The fit is shown in Figure 6 and yields k = 8.4(6) % h -1 , t i = 8.28(1) h, and n = 0.537 (3).…”
Section: Discussionmentioning
confidence: 93%
“…The 7 Li 1/T 1 (T) curve in Li 12 C 60 displayed in Figure 7 shows a single peak at T ∼ 400 K. This behavior differs from Li 6 C 60 and Na 6 C 60 [5,29] which shows two peaks, one around 150 K and the other around 400 K. A recent NMR investigation [29] showed that these two peaks reflect two thermally activated ion show a single occupancy [9]. When this structural transition occurs, ionic diffusion through the channel connecting the octahedral and tetrahedral interstices becomes possible.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, large Mgion conductivity was also observed in the Mg 2 C 60 compound, isostructural to Li 4 C 60 [25]. More recently, a detailed NMR and DC/AC conductivity study on the alkali-cluster intercalated Li 6 C 60 evidenced the presence of room temperature Li interdiffusive dinamics also in absence of fullerene polymerization, which is hampered upon the hydrogenation of the sample [5]. These findings support the possible applications of this class of compounds as solid-state electrolytes in novel ionic batteries [6,26,27,4].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, the temperature of the onset of desorption was reduced to about 250 -300 °C, well below the temperature (> 500 °C) at which hydrogen starts to desorb from pure fulleranes [33,34]. Optical spectroscopy, X-ray diffraction, neutron diffraction, NMR and Muon Spin Relaxation have been applied to probe the dynamics and structural changes that accompany ad-and desorption of hydrogen [23,[30][31][32][33][35][36][37][38][39]. Laser-desorption mass spectra of hydrogenated alkali-doped C60 solids show evidence for the presence of HnC60 (n up to 48) fulleranes [23]; other spectra show HnC60 + ions containing as many as 60 hydrogen atoms [32].…”
Section: Introductionmentioning
confidence: 99%